Shade Landscape for Efficient Building Air-conditioning Tree Layout Guidelines for the Three U.P. Diliman Building Units - Santos, Eunice D.; Zenaida Galingan (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Greatly air-conditioned buildings are those that consume the most electricity in the University of the Philippines—Diliman. Instead of typically cooling the indoors with air conditioner units, thermal comfort can be achieved by lessening the received heat of a building. Thus reducing the workload in air-conditioning and, likewise, the energy consumption.
A Shade Tree Layout Comprehensive Guidelines was made and used in designing the proposed cooling landscapes. The methodology of the thesis includes estimating the heat extraction capacities of the air-conditioner units and the shade trees. However, since the heat extraction of trees and air-conditioner units cannot be directly related, energy analyses were made through the Revit BIM software and Insight.
Actual characteristics of the canopy of the specified trees like having varying leaf sizes, gaps, and twigs cannot be replicated in Revit. As a result, mass objects treated as shading surfaces in Revit were made instead to replicate the tree canopies. The buildings’ framework (walls and floors) and basic building fixtures (doors and windows) were modeled along with the mass shading objects (serving as tree canopies), then energy analyses were run.
The Proposed Shade Landscape models showed lower total estimated annual Mean EUI (Energy Use Intensity) Values and Mean Energy Costs when compared to the Existing Landscape models. There are 3.10% energy savings for the Proposed Landscape in the Office of the University Registrar (OUR) when compared to its Existing Landscape While there are 1.33% savings in the Alumni Engineers Centennial Hall and 0.05% savings in the Institute of Mathematics. The limited methods in this undergraduate thesis is a preliminary study for building energy models and would qualify for greater potential in future studies provided with more resources.
includes appendices
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Cooling landscape; Landscape architecture -- Guidelines; Shade landscape